Success factors for B2B E-marketplaces in Malaysia / Farhana Md. Hilal - Md. Hilal, Farhana (2006)
The electronic business arena is highly dynamic and characterized by continuous evolution in technology, marketing concepts and effective business approaches. Business-to-business (B2B) electronic commerce, in particular, is evolving, especially in relation to virtual supply chain management and electronic marketplaces (e-marketplaces). Even Malaysia has a positive growth outlook in the growing number of electronic merchants on the local front. There are some providers managing e-marketplaces in Malaysia. Some of them have succeeded if measured according to their status in the Multimedia Super Corridor or in their listing in the Kuala Lumpur Stock Exchange (Bursa Malaysia). Responding to the phenomena, this research was conducted to analyse the factors that influence their successful sustainability. The aims are to identify the success factors that are most applicable for B2B e-marketplaces in Malaysia and determine the impact of identified factors to B2B e-marketplaces in Malaysia. This research used knowledge abstraction in an attempt to identify the factors and a field study was conducted via interviews and questionnaire survey on B2B providers. Targeted respondents are located from search engines and an online directory at www.eMarketplacedirectory.com. Nineteen targeted respondents are identified based on two basic characteristics. First, the company should be practicing business-to-business activities and second, perform business activities in Malaysia or including Malaysia. Based on secondary data, the researcher identified seven factors that contribute to the success of e-marketplaces in Malaysia which are neutrality/bias, target market, partnerships, building liquidity, culture, privacy and security, and technology. There were some limitations encountered during the course of the research. However, the findings indicated that five success factors are applicable to Malaysian business society whereas culture, privacy and security, and technology do not affect the success of B2B e-marketplaces in Malaysia.